When You Can't Afford to Wait for a Job: The Role of Time Discounting for Own-Account Workers in Developing Countries - Thiago Scarelli; David N. Margolis (Institute of Labor Economics (IZA), 2023)
Frictional labor markets impose a fundamental trade- off: individuals may work on their own at any time, but can only take a potentially better-paid wage job after spending some time looking for it, suggesting that intertemporal considerations affect how people choose their occupation. We formalize this intuition under the job search framework and show that a sufficiently high subjective discount rate can justify the choice for own-account work even when it pays less than wage work. With this simple model, we estimate a lower bound for the discount rate that is implicit in the occupational choice of urban own-account workers in Brazil. We find that at least 65 percent of those workers appear to discount the future at rates superior to those available in the credit market, which suggests constrained occupational choice. Finally, we show that the estimated lower bound of the preference for the present is positively associated with food, clothing, and housing deprivation.
Keywords: J22; J24; J31; J64; 330; own-account work; self-employment; developing countries; financial constraints; time discounting; Brazil